Pharmacokinetics of anastrozole and tamoxifen alone, and in combination, during adjuvant endocrine therapy for early breast cancer in postmenopausal women: a sub-protocol of the ‘Arimidex™ and Tamoxifen Alone or in Combination’ (ATAC) trial - Trialists' Group, The ATAC (Nature Publishing Group, 2001)
The ATAC trial evaluates in a randomized, double-blind design, Arimidex™ (anastrozole) alone or in combination with tamoxifen, relative to tamoxifen alone as 5-year adjuvant treatment in postmenopausal women with early breast cancer. Patients included in the pharmacokinetic (PK) sub-protocol had been in ATAC for ≥3 months, taking their medication in the morning and were 100% compliant for the preceding 14 days. Blood samples were collected 24 ± 4 h after last dose. Trough (C(min)) plasma concentrations of anastrozole, tamoxifen and desmethyltamoxifen (DMT) were measured by validated methods. The PK results were based on a total of 347 patients (131 anastrozole (1 mg o.d.), 111 tamoxifen (20 mg o.d.), 105 anastrozole and tamoxifen (1 and 20 mg o.d. respectively)). The geometric mean steady-state trough plasma concentrations of tamoxifen and DMT were statistically equivalent in patients receiving tamoxifen alone or in combination with anastrozole: geometric mean tamoxifen = 94.8 ng ml(−1)and 95.3 ng ml(−1)in tamoxifen alone and combination groups, respectively; geometric mean DMT = 265.1 and 277.6 ng ml(−1)in the tamoxifen and anastrozole and tamoxifen groups, respectively. The geometric mean anastrozole levels were 27% lower (90% Cl 20–33%;P< 0.001) in the presence of tamoxifen than with anastrozole alone. Baseline plasma oestradiol levels were not obtained in the PK sub-protocol, however, such information was available from a similar ATAC sub-protocol, which evaluated bone mineral density. Mean oestradiol levels were 21.3, 19.3, and 21.6 pmol l(−1)prior to treatment and 3.7, 20.9 and 3.6 pmol l(−1)after 3 months in the anastrozole, tamoxifen, and combination groups, respectively (n = 167). On-treatment values were below the detection limit (3 pmol l(−1)) in 43.6 and 38.5% of the anastrozole alone and anastrozole in combination with tamoxifen groups, respectively. As a result of (a) the lack of effect of anastrozole on tamoxifen and DMT levels and (b) the observed fall in blood anastrozole levels having no significant effect on oestradiol suppression by anastrozole, we conclude that the observed reduction in anastrozole levels by tamoxifen is unlikely to be of clinical significance when anastrozole and tamoxifen are administered together. © 2001 Cancer Research Campaign http://www.bjcancer.com